SEARCHING FOR GOD: THEOLOGY, IMAGINATION, BEAUTY AND THE ARTS - G.E. Thiessen (Acta Theologica)
This article offers a brief introduction on the development of, and key themes in the dialogue and interdisciplinary subject of faith, theology and the arts. It includes an outline of how the arts have become a central focus in contemporary theology as well as a historical review of how art is no longer viewed as ancilla theologiae but has its own and equal place regarding theology. Some reflections on the rendering of suffering and the cross in modern art as well as an examination of how the imagination and beauty are vital in the life of faith and in the arts conclude the article.